Description of a home visits service for elderly homebound patients and analysis of the determinants of its use. - Dueñas-Espín, Iván (2021)
Background: We developed an innovative service of home health care visits for homebound patients, assigned to a health care center in Quito-Ecuador. Objectives: (i) To describe the service and evaluate its adjustment to the primary care model, (ii) to describe the flow of service processes to subsequently adopt or adapt it in other health care facilities, (iii) to identify the determinants of home visit utilization; and (iv) to internally validate the fiability of a scoring system, based on those determinants. Subjects and methods: We performed an observational longitudinal retrospective study and developing of a scoring system. We analyzed the sociodemographic and clinical characteristics of the patients during the first home visit and counted the number of home visits per patient 18 months later. Through negative binomial regression models, we identified the determinants of home visits utilization. The adjusted β-coefficients were transformed into a score and validated internally by calculating the area under the curve. Results: 120 patients received 285 home visits after 18 months, 70% were women with a mean age of 83 years. Nine patients received 75 home visits. Age, marital status, multimorbidity-polypharmacy, and the initial performance of clinical procedures were independent determinants of ≥4 home visits per year. The area under the curve score was 0.80 (95% CI = 0.78 to 0.82). Discussion y conclusion: Our home visit service to homebound patients resulted in an intervention that fit the primary care model. The flowchart allows it to be adopted or adapted in other health care facilities. Age, marital status, multimorbidity-polypharmacy and the performance of clinical procedures reliably predicted the service utilization.